Strategic Information System Planning at UMKM in Padalarang Village using Ward and Peppard Methods - Saputra, Yogi; Herlita, Aulia Nur; Nurpajriah, Ela Siti (CoreID Journal, 2023)
Currently, the advancement of information systems and technology offers numerous advantages to human existence, encompassing nearly every aspect of life, including strategic planning. Good strategic planning implementation will benefit the organizations that use it as well as commercial entities like small and medium-sized enterprises (UMKM). In Padalarang Village, the industry that can employ the greatest number of specialized workers is UMKM. There is no questioning UMKM's existence because it has demonstrated its ability to endure, act as a catalyst for the local economy, and grow it.  One of the communities in the Padalarangs Prefecture is Padalarang Village. West Java's West Bandung district has potential in the UMKM field, and the strategy's village layout supports this idea. The purpose of the research was to develop an information system strategy for Padalarang Village's UMKM, with the goal of motivating UMKM to enhance benefits using information systems. The Ward and Peppard methods were employed, with phases for SWOT, Value Chain, and Five Force analysis. Interviews and questionnaires were sent to pertinent parties throughout the data collecting phase. The study's conclusion is that UMKM needs to be proficient in the use of information technology to become an innovation to develop its business.